The using CASE tools in the software development life cycle - A. Burnashev, Rustam; I. Enikeev, Arslan (International Journal of Engineering and Technology, 2018)
In article we give a review of the implemented CASE tool, the essence of which is to identify the necessary system properties of the software and hardware applications to provide customers with the best option that best suits their needs. The CASE tool uses telemetry, allowing developers to remotely identify and process the required characteristics of workstations by their software and hardware parts on the network. The received characteristics about workstations allow the developer to make a decision in the choice ofÂ technologies and tools in the design and development of the future software products. These apparatuses shape an incorporated advancement condition permitting the PC helped improvement of various applications in the proper field. The coordinated condition which we consider in our report speaks to the blend of SWI-PROLOG, C# and Information Base Administration Framework (DBMS) PostgreSQL. Because of the examination we got the most fundamental and imperative qualities of workstations that influence the incorporation and usage of programming item.Â Â Â